Valuing and Managing the Philippines’ Marine Resources toward a Prosperous Ocean-Based Blue Economy - Azanza, Rhodora V (Archīum Ateneo, 2017)
The ocean-based “blue economy” is a significant part of the Philippine economy that has largely been taken for granted despite its enormous potential. It is of critical importance to a substantial segment of our population dependent on the seas and coastal resources for their livelihood and sustenance, appreciably enlarge the country’s wealth, and significantly contribute to its gross domestic product. This paper attempts to review the major issues concerning marine ecosystems in relation to the country’s pursuit of the blue economy. It discusses the economic and social activities in relation to the seas and coastal areas, and provides updated estimates of the real value of the country’s marine ecosystems’ goods and services. Based on primary and available secondary data, the marine ecosystems (excluding the continental shelf) can contribute a conservative monetary value of US$ 966.6 billion to the economy. In light of the risks and threats to the blue economy, the paper further discusses the country’s current national initiatives and involvement in regional collaborations toward ensuring its health and sustainable development. Given the Philippines’ vast largely untapped potential, a recommendation for the creation of a Department of Marine Resources, separate from the Department of Agriculture, seems in order.